AfHNS fellowship: Model to improve access to head and neck cancer care in Africa and developing countries. Issue 10 (29th May 2021) - Fagan, Johannes J.; Otiti, Jeff; Onakoya, Paul A.; Diom, Evelyne; Konney, Anna; Gebeyehu, Melesse; Aswani, Joyce; Baidoo, Kenneth; Koch, Wayne M.
Abstract: Background: Head and neck cancers occur predominantly in developing countries where access to care is poor. Sub‐Saharan Africa has <20 head and neck surgeons for >1 billion people and has only two fellowship training programs. Methods and results: The AfHNS Head and Neck Fellowship is being introduced to accelerate training of African surgeons to improve access to resource appropriate cancer care. By avoiding fixed time‐in‐training and single training sites, training can be offered at multiple centers in Africa, even with lower patient volumes. It also creates opportunities for accredited international surgical outreach programs to contribute to training. Conclusions: Having prescribed reading and appropriate Entrustable Professional Activities that are assessed through Workplace Based Assessment, and having a summative virtual oral examination ensures that fellows are fit‐for‐purpose to practice in an African resource‐constrained setting. Other developing countries are encouraged to adopt a similar approach to expanding head and neck cancer services.